ENSURING ECONOMIC SECURITY OF AGRICULTURE (World Economics and Finance Bulletin, 2024)
The article reflects the relevance of the problem of ensuring the economic security of agricultural enterprises in the prism of rational land use in the conditions of transformations in the system of land relations. It is proved that land resources for business entities in the agricultural sector are one of the main factors of production and reproduction process, a natural resource and an object of socio-economic relations. The features of the land as a means of production are outlined. It is revealed that the conditions of rational land use are the concentration of threats to the economic security of agricultural enterprises. The role of the factor of rational land use in the system of economic security is determined.
Keywords: economic security; sustainable development; integrated agricultural formations